An Evaluation of Entrepreneurship Intention Theories - Mwange, Austin (IJRDO - Journal of Social Science and Humanities Research, 2018)
Entrepreneurship and entrepreneurship intentions studies are anchored on several competing and complementing theories. Therefore, there is need to understand these theories, especially for researchers, when conducting studies focusing on entrepreneurship intentions. It is against this background a study to critically evaluate selected theories that explain entrepreneurship intentions was conducted. This was a literature review based study. A profile of theories used in entrepreneurship intention studies was conducted and an analysis of each entrepreneurship intention theory was done. The study revealed that the most used theories are: The Theory of Reasoned Action, cross-cultural cognitive model creation Shapero’s Model of entrepreneurship intentions; The Integrated Model of Entrepreneurial Intentions; the Theory of Planned Behaviour and the structural model of entrepreneurial intent from Lüthje and Franke.